Solar‐Thermal Driven Self‐Heating of Micro‐Supercapacitors at Low Temperatures. Issue 12 (29th October 2018) - Sun, Yinglun; Ma, Pengjun; Liu, Lingyang; Chen, Jiangtao; Zhang, Xu; Lang, Junwei; Yan, Xingbin
Abstract : The solar‐thermal conversion of sunlight into heat has received considerable attention due to its low cost and high conversion efficiency. Microsupercapacitors (MSCs) are a promising class of microscale power sources for microelectronic devices, but low‐temperature operation is a huge challenge for their potential applications due to sluggish diffusion kinetics. Here, a simple strategy of adhering a graphene photothermal film on the backside of a model MSC to realize the device self‐heating at low temperatures is demonstrated. At an extremely low ambient temperature of −50 °C, graphene film can increase the actual operating temperature of MSC to −16.5 °C under irradiation of 1 sun. Solar‐driven self‐heating resulted in a 4.5‐fold increase in the specific capacitance, a 2.7‐fold increase in the rate capability, and a 2.8‐fold increase in the energy density without compromising the cyclic stability. This work presents a new application for solar energy and a new approach to improve the overall performance of MSCs at low temperatures. Abstract : Combining the photothermal effect of graphene with a microsupercapacitor to boost its performance at low temperatures is proposed. A graphene film as a photothermal film, which is attached on the backside of a model microsupercapacitor, can convert sunlight into thermal energy to increase the internal temperature of the microsupercapacitor, thereby accelerating ion mobility in electrolytes and ultimately enhancing the electrochemical performance of the device.